2010
DOI: 10.1016/j.ceca.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of SERCA pump and ryanodine-sensitive stores to presynaptic residual Ca2+

Abstract: The presynaptic Ca2+ signal, which triggers vesicle release, disperses to a broadly distributed residual [Ca2+] ([Ca2+]res) that plays an important role in synaptic plasticity. We have previously reported a slowing in the decay timecourse of [Ca2+]res during the second of paired pulses. In this study, we investigated the contributions of organelle and plasma membrane Ca2+ flux pathways to the reduction of effectiveness of [Ca2+]res clearance during short-term plasticity in Schaffer collateral terminals in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…These measurements were made from records of fEPSP slopes recorded in CA1 stratum radiatum following surgical isolation of Schaffer collateral axons from their somata in CA3. In our previous studies (Schiess et al, 2006; Scullin and Partridge, 2010; Scullin et al, 2010), we have used both fEPSP slope ratios and population spike (PS) amplitude ratios to determine PPF at the SC-CA1 synapse with results that are comparable to those observed in figures 1A and C. As discussed in Experimental Procedures, due to our interest in the presynaptic [Ca 2+ ] res we chose to use measurements of PS amplitude for the remaining analyses in this study.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…These measurements were made from records of fEPSP slopes recorded in CA1 stratum radiatum following surgical isolation of Schaffer collateral axons from their somata in CA3. In our previous studies (Schiess et al, 2006; Scullin and Partridge, 2010; Scullin et al, 2010), we have used both fEPSP slope ratios and population spike (PS) amplitude ratios to determine PPF at the SC-CA1 synapse with results that are comparable to those observed in figures 1A and C. As discussed in Experimental Procedures, due to our interest in the presynaptic [Ca 2+ ] res we chose to use measurements of PS amplitude for the remaining analyses in this study.…”
Section: Resultsmentioning
confidence: 93%
“…We have previously demonstrated that there is significant supra-linear summation of [Ca 2+ ] res during paired-pulses in the adult rat hippocampus such that the ratio of ∫ΔF/F 0 resulting from paired-pulses is more than twice that elicited by a single pulse (Schiess et al, 2006). While our ΔF/F 0 measurement does not directly assess the Ca 2+ that is responsible for vesicular release, it is representative of the saturation of the mechanisms that determine the timecourse of presynaptic [Ca 2+ ] res (Scullin and Partridge, 2010). Furthermore, we and others have shown [Ca 2+ ] res to be a critical determinant of the facilitation of the post-synaptic response (Schiess et al, 2010; Wu and Saggau, 1994; Zucker and Regehr, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were performed in coronal hippocampal slices prepared from a total of 79 P21 – 28 C57BL/6 mice ( Mus musculus ) as previously described (Scullin and Partridge, 2010). Briefly, animals were deeply anaesthetized by i.p.…”
Section: Methodsmentioning
confidence: 99%